A HYBRID FUZZY-MONTE CARLO SIMULATION APPROACH FOR ECONOMICAL ASSESSMENT OF THE IMPACT OF ERP TECHNOLOGY (Journal of Information and Communication Technology, 2012)
Enterprise Resource Planning (ERP) is believed to be able to support the effectiveness of a business process of either goods or services through reliability of information flow among the different function areas of multiple business units. Many managers know this benefit, but they are still vacillating to decide to invest an ERP in their structure. This vacillation comes from considerations of budget and uncertainty or risk of economic constraints. Therefore, taking into account the ERP contribution or impact both of tangible and intangible values through cost and benefit analysis is essential for the success of this project. In this paper, we will reveal how the factor of cost and benefit in an economical assessment can be applied to the ERP investment plan. The expected increase of market share due to customer satisfaction is determined in expressions of information cycle time and quality between customers and suppliers by using a Fuzzy rule-based system. Furthermore, a Monte-Carlo simulation method is used to consider such uncertainties in calculating the expected net present value (NPV).